Mosaic Deletions of Known Genes Explain Skeletal Dysplasias With High and Low Bone Mass. (5th July 2022) - Muurinen, Mari; Taylan, Fulya; Tournis, Symeon; Eisfeldt, Jesper; Balanika, Alexia; Vastardis, Heleni; Ala‐Mello, Sirpa; Mäkitie, Outi; Costantini, Alice
ABSTRACT: Mosaicism, a state in which an individual has two or more genetically distinct populations of cells in the body, can be difficult to detect because of either mild or atypical clinical presentation and limitations in the commonly used detection methods. Knowledge of the role of mosaicism is limited in many skeletal disorders, including osteopathia striata with cranial sclerosis (OSCS) and cleidocranial dysplasia (CCD). We used whole‐genome sequencing (WGS) with coverage >40× to identify the genetic causes of disease in two clinically diagnosed patients. In a female patient with OSCS, we identified a mosaic 7‐nucleotide frameshift deletion in exon 2 of AMER1, NM_152424.4:c.855_861del:p.(His285Glnfs*7), affecting 8.3% of the WGS reads. In a male patient with CCD, approximately 34% of the WGS reads harbored a 3710‐basepair mosaic deletion, NC_000006.11:g.45514471_45518181del, starting in intron 8 of RUNX2 and terminating in the 3′ untranslated region. Droplet digital polymerase chain reaction was used to validate these deletions and quantify the absolute level of mosaicism in each patient. Although constitutional variants in AMER1 and RUNX2 are a known cause of OSCS and CCD, respectively, the mosaic changes here reported have not been described previously. Our study indicates that mosaicism should be considered in unsolved cases of skeletal dysplasia and should be investigated with comprehensive and sensitive detection methods. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. Abstract : In this study two mosaic deletions were identified in two patients with skeletal dysplasia. After isolating genomic DNA from peripheral blood (steps 1‐2), whole‐genome sequencing was performed (step 3) and led to the identification of two somatic deletions in two genes already linked to skeletal conditions. Droplet digital PCR was subsequently used to validate these deletions and carry out a sensitive quantification of the level of mosaicism (step 4).